2013
DOI: 10.1097/aap.0b013e318279499d
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine Administered With Lidocaine Solution Does Not Worsen Intrathecal Lidocaine Neurotoxicity in Rats

Abstract: Intrathecal epinephrine prolonged the action of intrathecal lidocaine but did not worsen lidocaine-induced histological damage and functional impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…[21,24,25] In peripheral nerve blocks, epinephrine shows some analgesic effects in combination with short-acting and intermediate-acting local anesthetics such as lidocaine, but similar effects have not been observed in combination with long-acting local anesthetics such as bupivacaine and ropivacaine. [22,23] An epinephrine solution of 25 µg/ml may be an effective marker for intravascular injection of a local anesthetic. It has been suggested that this dose may also transiently increase blood flow to the peripheral nerve itself, probably due to its β-adrenergic effects.…”
Section: Discussionmentioning
confidence: 99%
“…[21,24,25] In peripheral nerve blocks, epinephrine shows some analgesic effects in combination with short-acting and intermediate-acting local anesthetics such as lidocaine, but similar effects have not been observed in combination with long-acting local anesthetics such as bupivacaine and ropivacaine. [22,23] An epinephrine solution of 25 µg/ml may be an effective marker for intravascular injection of a local anesthetic. It has been suggested that this dose may also transiently increase blood flow to the peripheral nerve itself, probably due to its β-adrenergic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Applied as an adjuvant, adrenaline is a relatively safe drug. Studies in rats have not showed an increase in the percentage of either histological or functional nerve damage after perineural administration of a mixture of lidocaine and adrenaline [ 11 ]. It should be remembered, however, that adrenaline may potentiate the vasoconstrictor effect, especially in relation to long-acting LAs, thus prolonging the toxic effect of LA on axons [ 12 , 13 ].…”
Section: Adrenalinmentioning
confidence: 99%
“…However, studies have shown that local anesthetics administered intrathecally may induce cell swelling, atrophy, edema, axonal degeneration, the appearance of myelin ovoid’s, and macrophage infiltration, 1 and continuous application of not only high concentrations but also normal clinical doses 2 of local anesthetics can cause neurotoxicity. 3 , 4 , 5 Although the potential neurotoxicity of local anesthetics has been investigated for many years, the mechanisms by which they induce neuronal injury are not fully understood. Therefore, it is necessary to identify these mechanisms to develop effective clinical strategies with which to prevent adverse outcomes after local anesthetic administration.…”
Section: Introductionmentioning
confidence: 99%